KEBERHASILAN PENGEMBANGAN TERNAK SAPI POTONG MELALUI POLA PENGEMBANGAN MODAL USAHA (KUPS) - Winarso, Bambang (Politeknik Negeri Lampung., 2015)
Government policies in helping dairy farmers in an effort to meet the capital needs of breeding them is through a policy program Kredit Usaha Pembibitan Sapi (KUPS). KUPS is skim credit used to finance the development of cattle breeding and dairy cattle by businesses with subsidized interest rates. The problems that the distribution KUPS seen through the eyes of a banking institution is (a) the availability of information prospective potential borrowers are still minimal (b) the legality of ownership of assets (c) cattle breeding company still slightly. KUPS program has been rolled out since 2010, meaning that until 2014 the program has been running five (5) years. But the realization of its lending until September 2014, reached 15.42% of the amount of the ceiling of Rp 4.00 trillion. The realization can be said to be too small or fails. Of course there is the small achievements of the bank as an institution that is authorized to distribute funds would need to act professionally and carefully. Given the experience of lending a mass program past such cases KUT (Kredit Usaha Tani) end up with less encouraging. Instead the main purpose of the program is awakened, just the opposite of credit are understood as government social assistance by the debtor (the farmer). So it is very natural that the bank hand is always cautious. The study was conducted in West Sumatra in 2014, data analysis used data a simple cross-tabulation using the primary data and secondary data from interviews with respondents either breeders penmanfaat KUPS and banking institutions as channeling KUPS Keywords: Beef Cattle Development, Venture Capital, KUPS